Lumbung Padi Indonesia dan Kemiskinan: Studi Kasus Kabupaten Kota di Jawa Timur - Diana Rizky Safitri; Estro Dariatno Sihaloho (Ekonomis: Journal of Economics and Business, 2020)
This research aims to determine whether the area called as a rice barn in Indonesia can alleviate the poverty problem in the region. East Java is Indonesia's rice barn with a total production of 16.1% of the total rice production in Indonesia. This research uses panel data and fixed-effect methods with quantitative analysis. The data used is secondary data obtained from the website of the Ministry of Agriculture of the Republic of Indonesia (KPRI) and the Indonesian Bureau of Central Statistics (BPS) with data on city districts in 2014 - 2017. This research uses the variable percentage of poverty in the Regency of East Java City as the dependent variable, the percentage level farmer productivity, percentage of agricultural land area, and the level of community consumption in East Java as independent variables. The results of the research using panel data and the fixed-effect method show that the production variable has a negative and significant impact on the percentage of community poverty in East Java Regency.